Use of Augmented Reality in the Design of Land Facilities Supporting Nuclear-Powered Submarines - Cristiane Lopes Canuto; Rodrigo Toth Reis; Paulo Caixeta de Oliveira; Douglas Brandão Baroni; Thiago Rampim de Marcos; Sad Sandrini Borsoi; Gabriel Nóbile Diniz (Brazilian Journal of Radiation Sciences, 2025)
This paper addresses the potential applications of Augmented Reality (AR) in the design and operation of nuclear facilities, focusing on terrestrial support facilities for nuclear-powered submarines. The inherent complexity in developing these submarines demands continuous innovations, including the design of their land-based support facilities. AR emerges as a promising perspective, allowing high-tech approaches to specific challenges in the design and operation of these facilities. The study presents an initial application of AR aimed at evaluating the integration and functionality of the proposed setup (computer, AR smart glasses, application, file conversion and transfer processes, etc.). Once the operability of this setup is validated, a list of applications (in development) is proposed to highlight the potential contributions of AR in the development of land-based support for nuclear-powered submarines. To validate the exploratory approach methodology, the proposed initial AR application includes the demonstration and display of three-dimensional models and their integration into the physical environment using commercial AR smart glasses and application. The results of this initial application suggest promising prospects for future applications. The list of AR applications under development ranges from the design phase to operation, including nuclear licensing, construction phase, operation, safeguards, physical protection, and quality assurance. It is concluded that the use of AR has potential to contribute to the development of land-based support facilities for nuclear-powered submarines, although further studies are needed to confirm its practical application and effectiveness.